Antimicrobial activities of piper betle endophytes / Rohana Mat Nor ...[et al.] - Mat Nor, Rohana; Ab Rahman, Zainon; Bastian, Muhd Nur Mansur; Mohd Noor, Zainon (2006)
Evidence had shown that microbial endophytes are capable of producing secondary metabolite(s) similarly to that of their host plants (Strobel & Daisy. 2003). Therefore, this study was performed to compare the antimicrobial activities produced by Piper betle endophytes with the bioactive substances of their host plant, which had previously been studied. Plant samples were collected from three different locations. The inner soft tissues were cultured onto nutrient agar and potato dextrose agar to isolate bacterial and fungal endophytes. 14 endophytes were successfully isolated. which were later fermented for two weeks. The fermentation broth was subjected to bioassay tests using disc diffusion agar method every two days of the fermentation process. The tests were against eight ATCC strains. Two isolates were found moderately active against Aspergillus niger ATCC 16404 after six fermentation days. AII other isolates did not show any activity against tested microorganisms. The findings showed that P. betle endophytes produced different bioactive metabolites from its host plant which was found to be strongly active against Bacillus subtilis but no activity against A. niger.